SOA : learning from the past to disrupt the future easier to manage and built for change. - Champion, Kerry (SOA webservices journal.)
Service oriented architecture (SOA) is an often-used term in today's IT organizations. Some surveys have shown that half of all Fortune 500 companies are actively pursuing an SOA in some form or another, many instituting it as their fundamental design concept.